The Functoin of Binary Opposition in Validation of Lasting Persian Couplets - Hamid Jafari GhariyehAli (مطالعات زبانی و بلاغی)
Binary opposition is a rhetorical device employed for meaning-making and word arrangement in languages and their versification. In structuralism, binary oppositions contribute significantly to systematic language composition as they entails cognitive deep structures. Considering their role in conveying meaning and literariness of speech, the present study is an investigation of binary oppositions in lasting Persian couplets. Indeed, a major aspect of couplets that contributes to their lasting impression is the emphasis they lay on human virtues, guidance, and enhancement of knowledge. The study primarily undertakes to show that certain lexicons play a key role in constructing couplets and help dig into underlying layers of the verse and the speaker’s thought. Therefore, key questions are how binary oppositions function in composing lasting couplets and to what extent they convey the poet's perspective. Results of our analytic and descriptive interpretations reveal that poets are deeply concerned with asymmetric elements that make up the overall message of the literary work. In other words, these word elements facilitate collocations in the axis of combination and contribute to the brevity and condensation of language. They, in fact, help retain brevity without disruption of the meaning. Binary oppositions may carry an elevated sense of meaning that encourages reflection and meditation. They also arouse a sense of awe in the reader through imagery, which turns couplets into a more viable medium with high exemplary functioning in folk literature.